مبدأ المسؤولية في ضوء الحكم الراشد "دراسة تحليلية": The Principle of Responsibility in the Light of Good Governance "An Analytical Study" - A Mahmoud , Belal J; bin Artalim Zaim, Muntaha (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص معايير الرشاد في النظام السياسي الإسلامي كثيرة، منها شرعية المحاسبة والمسؤولية، وأهمية هذا المعيار تتجلَّى من كونه أحدَ صور التكافل السياسي الذي أرسى الإسلام مبادئه، حيث إنَّه يرتكِزُ على إشراك الحاكم والمحكوم في إدارة شؤون الحكم، وأن ليس أحدا في النظام الإسلامي مُعْفًى من المسؤولية؛ ما يُفضِي بدوره إلى تقويم الحاكم والمحكوم على حدٍّ سواء. ويُظْهِرُ مشكلةَ البحث التساؤلُ عن التصور الإسلامي لهذا المبدأ، وما يثوِّره هذا التساؤل من القضايا ذات الصلة، نحو: ما الأسس التي تنهض بالمسؤولية وفقا للتصور الإسلامي؟ وما علاقته بفروض الكفايات والتي من أهمِّها ما يتعلق بالنظام السياسي؟ ثمَّ هل تقتصر المسؤولية على أحد دون غيره، وعلى الآخرة دون الدنيا؟ وحيث إن المسؤولية أحد صور التكافل السياسي، فما مراتب المسؤولية في الحكم الراشد؟ ويهدف البحث إلى بيان التصور الإسلامي لمعيار المسؤولية، والكشف عن مستوياته في الحكم الراشد. وفي سبيل ذلك سلك الباحثان المنهجين الاستقرائي والتحليلي. وانتهى البحث إلى جملة من النتائج، من أهمها: ابتناء المسؤولية على ركني التكليف والمحاسبة، وأن المخاطب بالمسؤولية ثلاثة مستويات، هي: الحاكم والأمة والفرد، وكلٌّ منها يضطلع بتكاليفَ تتَّسِق وإمكاناته، ويخضع للمحاسبة عليها. Abstract The criteria of guidance in the Islamic political system are many, including the legitimacy of accountability and responsibility, and the importance of this criterion is evidenced by the fact that it is one of the forms of political interdependence that Islam established its principles, as it is based on the involvement of the ruler and the ruled in the management of governance affairs, and that no one in the Islamic system is exempt from responsibility; Which in turn leads to the evaluation of the ruler and the ruled alike. The research problem shows the question about the Islamic conception of this principle, and what this question raises from related issues, towards: What are the foundations that promote responsibility according to the Islamic conception? And what is its relationship to the assumptions of competencies, the most important of which is what is related to the political system? Then is the responsibility limited to one person and not another, and to the afterlife rather than the world? Since responsibility is one of the forms of political interdependence, what are the levels of responsibility in good governance? The research aims to clarify the Islamic conception of the criterion of responsibility, and to reveal its levels in the good governance. To this end, the researchers followed the inductive and analytical approaches. The research concluded with a number of results, the most important of which are: responsibility is based on the two pillars of assignment and accountability, and that the responsibility is addressed to three levels: the ruler, the nation, and the individual, and each of them bears costs that are consistent with its capabilities, and is subject to accountability for it.